Electrocatalytic biofuel cell based on highly efficient metal-polymer nano-architectured bioelectrodes. (September 2017) - Mishra, Prashant; Lakshmi, G.B.V.S.; Mishra, Sachin; Avasthi, D.K.; Swart, Hendrik C.; Turner, Anthony P.F.; Mishra, Yogendra K.; Tiwari, Ashutosh
Abstract: Bioenergy based devices are rapidly gaining significant research interest because of growing quest for future alternative energy resources, but most of the existing technologies suffer from poor electron transfer and slow mass transport, which hinder the fabrication of realistic high-power devices. Using a versatile strategy, here we have demonstrated the fabrication of nanoparticle-polymer framework based bioelectrocatalytic interfaces which facilitate a high mass-transport and thus offers the simple construction of advanced enzyme-based biofuel cells. It has been shown that a gold nanoparticle-structured polyaniline network can be effectively used as an electrical cabling interface providing efficient electron transfer for bio- anode and cathode. The resulting bioelectrodes are capable of excellent diffusional mass-transport and thus can easily facilitate the design of new and highly efficient membrane-less advanced bioenergy devices. The biofuel cell delivers a high-power density of about 2.5 times (i.e., 685 µW cm −2 ) and open circuit voltage of 760 mV compared to conventional conducting polymer-based biofuel cells. Graphical abstract: The illustration of the biofuel cell set-up using bioanode, GOx/Au@PANI and biocathode, Laccase/Au@PANI nanoarchitectured bioelectrodes. Highlights: A high mass-transport bioelectrocatalytic interfaces based on a nanoparticle-polymer framework is investigated. The compatibility of bio- anode and cathode was tested with electrochemical methods. The bioelectrodes can offer highly efficient membrane-less bioenergy devices. The biofuel cell delivers a high-power density and open circuit voltage compared to conventional polymer-based biofuel cells. The nanoparticle-polymer framework could significantly accelerate developments in the field of high-performance bio-energy devices.